Eighth Nerve Dysfunction in Type 2 Diabetes Mellitus - Virgin, Joena M; Rajendran, Ramesh (International Journal of Medical Research and Review, 2017)
Introduction: Hearing impairment is one of the under-recognized complications of diabetes that affects the cognitive performance and quality of life. The study was conducted to estimate the prevalence of hearing impairment and analyze the type, degree and pattern of hearing impairment in diabetic population. Materials and Methods: The study was conducted as a case-control study including 50 diabetic patients and 20 healthy individuals after exclusion of confounding factors. Hearing assessment was done using pure tone audiometry. Results: The prevalence of hearing impairment in diabetics of age 35-65 years was 74% compared to normal population (15%). 7 out of 13 diabetic patients in the age group of 35-45, 19 out of 37 diabetics in the age group of 45-55 & 11 out of 13 diabetics in the age group of 55-65 had hearing impairment. 9 out of 12 diabetic patients having HbA1c of < 7 and 28 out of 38 diabetic patients having HbA1c of >7 had hearing impairment. 21 out of 27 patients with diabetes duration of <1 year, 6 out of 11 patients with diabetes duration of 1-5 years, and 10 out of 12 patients with diabetes duration >5years had hearing impairment. Out of 37 diabetic patients who had hearing impairment, 24 (64%) had diabetic neuropathy. Conclusion: Eighth nerve dysfunction is common among diabetics. Its prevalence among the diabetics increases with age and positively correlates with the duration of diabetes and presence of diabetic peripheral neuropathy. However, its prevalence did not show positive correlation with the HbA1c levels.